2020
DOI: 10.3390/nu12061740
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Fatty Acid Composition of Allergic and Non-Allergic Mothers: The Ulm SPATZ Health Study

Abstract: The aim of this study was to determine the differences in human milk fatty acid composition in relation to maternal allergy within a large birth cohort study using statistical methods accounting for the correlations that exist in compositional data. We observed marginal differences in human milk fatty acid composition of allergic and non-allergic mothers. However, our results do not support the hypothesis that human milk fatty acid composition is influenced by allergy or that it differs between mothers with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While several infant-related factors (i.e., birth weight, gestational age, and infant age) are known to affect nutritive and non-nutritive components of breast milk, there is limited or conflicting evidence regarding the possible role of maternal factors (i.e., maternal lifestyle, obstetric history, and medical conditions), except for mother’s diet that significantly influences milk composition. For example, at present there is inconsistent evidence that maternal atopy/allergy may affect breast milk composition of interleukins, growth factors, pro-inflammatory markers, cytokines, and fatty acids [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, it has been reported that human milk growth factors and cytokines levels varied between populations for unknown reasons, and breast milk mediator levels declined at different rates postpartum, suggesting specific biological roles for human milk growth factors and cytokines in early postnatal development [ 30 ].…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%
“…While several infant-related factors (i.e., birth weight, gestational age, and infant age) are known to affect nutritive and non-nutritive components of breast milk, there is limited or conflicting evidence regarding the possible role of maternal factors (i.e., maternal lifestyle, obstetric history, and medical conditions), except for mother’s diet that significantly influences milk composition. For example, at present there is inconsistent evidence that maternal atopy/allergy may affect breast milk composition of interleukins, growth factors, pro-inflammatory markers, cytokines, and fatty acids [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, it has been reported that human milk growth factors and cytokines levels varied between populations for unknown reasons, and breast milk mediator levels declined at different rates postpartum, suggesting specific biological roles for human milk growth factors and cytokines in early postnatal development [ 30 ].…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%
“…Fatty acids are classified by their carbon (C) chain length and degree of desaturation, each of which differs content in living cells or milk [7,8]. Long-chain (LC) fatty acids refer to fatty acids with a chain length of 11/12-20 carbons and are precursors of various lipids that participate in various physiological processes, e.g., cellular metabolism, energy homeostasis, and cell proliferation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Research from Germany [ 6 , 7 ], Italy [ 8 , 9 ], China [ 10 ], New Zealand [ 11 , 12 ], Iceland [ 13 ], India [ 14 ], and Spain [ 15 ] has revealed that HM composition varies depending on maternal food consumption habits, in addition to the maternal gestational age, lactation period, genetics, and life-style [ 16 , 17 ]. Moreover, maternal diet may play a role in shaping the infant gut microbial colonization by modulating the HM composition [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%